PRESERVASI JALAN NASIONAL SIMPANG LAGO-SIMPANG BUATAN KABUPATEN SIAK BERDASARKAN UMUR SISA PERKERASAN - Benny Hamdi Rhoma Putra; Yosi Alwinda; M. Rilly Aka Yogi (Politeknik Negeri Semarang, 2022)
Tanjung Buton Mengkapan Port is one of significant transportation node for Riau citizen, especially for Pekanbaru citizen. This port has some destinations within and outside the province of Riau. Access to reach this port through the Simpang lago and, Simpang Buatan. In order to keep good accessibility from and to this port, the road owner should develop a road management program on a regular basis. Programming can be set based on the Remaining Service Life, (RSL). The method which used to determin RSL in this study is the Interurban Road Management System (IRMS) method. The data required are deflection data generated from the Falling Weight Deflectometer (FWD) tools, average daily traffic data (ADT) and road geometric data. The results of the analysis showed that the smallest RSL was 0.012 years old at STA 14+220 and the Biggest RSL was 12.35 years old at STA 02+636. In addition, based on calculations, it is known that 50.3% of the road length requires overlay as preservation, 38.8% of the length of the road requires routine maintenance and 10.93% of the road needs reconstruction